2021
DOI: 10.1186/s12913-021-06536-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Veterans Health Administration utilization and pain persistence among soldiers treated for postdeployment chronic pain in the Military Health System

Abstract: Background Chronic pain presents a significant burden for both federal health care systems designed to serve combat Veterans in the United States (i.e., the Military Health System [MHS] and Veterans Health Administration [VHA]), yet there have been few studies of Veterans with chronic pain that have integrated data from both systems of care. This study examined 1) health care utilization in VHA as an enrollee (i.e., linkage to VHA) after military separation among soldiers with postdeployment ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(51 reference statements)
0
7
0
1
Order By: Relevance
“…For example, in comparing risk factors and health characteristics among veterans who did and did not receive VHA care, several studies show that VHA users report lower sociodemographic characteristics and higher comorbidities and disability than non-VA users. [35][36][37] In terms of risk for suicide among those with TBI by race/ethnicity, research among all cohorts (eg, military, general population) has been extremely limited. Our findings of significantly higher rates among AIAN individuals with mTBI are consistent with work by Mohatt et al, 38 who found a suicide rate of 66 per 100 000 person-years among AIAN veterans aged 18 to 39 years (2014-2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in comparing risk factors and health characteristics among veterans who did and did not receive VHA care, several studies show that VHA users report lower sociodemographic characteristics and higher comorbidities and disability than non-VA users. [35][36][37] In terms of risk for suicide among those with TBI by race/ethnicity, research among all cohorts (eg, military, general population) has been extremely limited. Our findings of significantly higher rates among AIAN individuals with mTBI are consistent with work by Mohatt et al, 38 who found a suicide rate of 66 per 100 000 person-years among AIAN veterans aged 18 to 39 years (2014-2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is in part related to demographic differences among those who do and do not seek VHA care. For example, in comparing risk factors and health characteristics among veterans who did and did not receive VHA care, several studies show that VHA users report lower sociodemographic characteristics and higher comorbidities and disability than non-VA users 35–37…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, 55.2% of the total sample and 72.6% of predicted high-risk respondents reported experiencing any 12-month SLE. This is likely to be an underestimate of significant stress exposure, though, given that we focused on commonly occurring acute stressors and did not assess either less-common acute stressors or chronic stressors known to occur to soldiers after leaving active duty (Adams, Meerwijk, Larson, & Harris, 2021; Kline, Ciccone, Falca-Dodson, Black, & Losonczy, 2011; Mansfield et al, 2011; Morin, 2011; Shen et al, 2016) and to be associated with elevated suicide risk (Hooley, Franklin, & Nock, 2014; Howarth et al, 2020; McFeeters et al, 2015; Nock et al, 2013). These results suggest that interventions to limit exposure to major stressors and, more importantly, to reduce vulnerability to these stressors might prevent a substantial proportion of the SAs that occur among high-risk soldiers after separation/deactivation.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] This hinders the implementation of evidence-based practice, as multimorbidity is the norm when managing chronic pain. [10][11][12] Thus a better understanding of high-risk presentations could help inform future policies and practice to ensure that those with the greatest clinical needs receive appropriate care without undue risk of addiction.…”
Section: Introductionmentioning
confidence: 99%